DataPublics : The Construction of Publics in Datafied Democracies - Jannie Møller Hartley; Jannick Kirk Sørensen; David Mathieu (Bristol University Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence This book addresses new challenges to the formation of publics in datafied democracies. It proposes a fresh, complex and nuanced approach to understand'datapublics'by considering datafication and public formation in the context of audience, journalism and infrastructure studies. The tightly woven chapters shed new light on how platforms, algorithms and their data infrastructure are embedded in journalistic values, discourses and practices, opening up new conditions for publics to display agency, mobilize and achieve legitimacy. This is a seminal contribution to debates about the future of media, journalism and civic practices.